The Complete Care Model and Glycemic Control in California State Prisons. (October 2020) - O'Laughlin, Diane M.; Rose, Jordan
Since integrating the chronic care theory in 2008 and the complete care model (CCM) in 2015, the California Department of Corrections and Rehabilitation (CDCR) has seen steady improvement in health care–related mortality. However, comparing glycated hemoglobin (HbA1c) levels for the 2 years pre- and the 2 years post-CCM shows the glycemic control for diabetes patients has not significantly changed. Findings suggest that additional components of the theory will need to be incorporated into the CCM to achieve CDCR's progressive goal of 90% of their diabetes patients having HbA1c levels less than 8%. Authors recommend specific direction for further research and development of the CCM in order to reach patient care goals associated with the full adoption of the chronic care theory.